Interpretation biases in chronic pain patients: an incidental learning task. (18th December 2014) - Khatibi, A.; Sharpe, L.; Jafari, H.; Gholami, S.; Dehghani, M.
Abstract Background The aim of this study was to investigate the impact of chronic pain on interpretation bias for ambiguous faces, using a recently developed paradigm with ecologically valid stimuli. Methods Fifty patients with chronic pain and 25 healthy controls were trained to respond to probes following the presentation of happy or painful faces, using an incidental learning task. During a test phase, ambiguous faces were presented. The degree to which participants were faster to respond to probes presented where painful (rather than happy) faces had previously been presented was taken as an indication of the interpretation bias towards painful faces. Results All participants had learnt the originally presented contingency. As predicted, chronic pain patients showed a greater bias towards interpreting ambiguous faces as painful than control participants. Further, there were correlations between fear of pain and catastrophizing and interpretation bias, indicating that participants with higher fear of pain and higher scores on a measure of catastrophizing were more likely to interpret ambiguous faces as painful. Severity of pain was inversely associated with increased interpretation bias for pain. Conclusion These results show clear evidence that chronic pain patients do demonstrate an interpretation bias towards painful faces and that this bias is greater for those who catastrophize more and have higher levels of fear of pain, but experienced less pain in the preceding week. Given the recent potential shown for interventions that modify cognitive biases, this paradigm would seem to be well suited to future efforts to modify interpretation biases in pain.